Content Analysis Speaking Materials in English Textbook Based on 2013 Curriculum for the First Grade Student at Vocational High School - Rezkiawati Nazaruddin (EDUVELOP, 2017)
This research aimed to analyze Speaking material in English textbook based on 2013 Curriculum for The First Grade Student at Vocational High 4 Makassar. The research method of this research was qualitative descriptive. The object of this research consists of English textbook and focus with Speaking material for the first grade based on 2013 Curriculum. The sample of the research was taken by using Checklist. To know how the relevancy the English textbook with 2013 curriculum that have been dealing with government. The researcher using 2 checklist the first was table to know the relation between speaking material in syllabus of 2013 curriculum and the second was table documentary checklist table to know how the relevance of materials to the curriculum criteria, and the result of the research showed by percentages. Having analyzed the data and the rubric scoring tabulation of this research, it was found that the degree of suitability of Buku Bahasa Inggris an English text book used by First grade students of Vocational High School was 75%. The Researcher concluded that the textbook were logic and can be implemented as a learning source in the classroom. Although it still needs some revision to make it better. During the researcher doing this research, actually the researcher does not face a problem, because the researcher just analyzing and collecting the data by checklist so, the researcher could does this research have done.